Acanthochondria cyclopsetta Pearse, 1952 and A. alleni n. sp. (Copepoda; Cyclopoida; Chondracanthidae) from flatfish hosts of the U.S.A., with comments on the taxonomic position of A. zebriae Ho, Kim & Kumar, 2000 and A. bicornis Shiino, 1955 and the validity of Pterochondria Ho, 1973 - Tang, Danny; Kalman, Julianne E.; Ho, Ju-Shey (Zootaxa, 2010)
A redescription of Acanthochondria cyclopsetta Pearse, 1952 (Copepoda; Chondracanthidae), hitherto reported only from the Mexican flounder, Cyclopsetta chittendeni Bean (Pleuronectiformes; Paralichthyidae), from Padre Island in the Gulf of Mexico, is presented based on female specimens from the spotfin flounder, Cyclopsetta fimbriata (Goode & Bean), collected off the coast of South Carolina, U.S.A. Furthermore, a description of the male of A. cyclopsetta is provided for the first time. Acanthochondria alleni n. sp. is also described based on specimens of both sexes collected from the fantail sole, Xystreurys liolepis Jordan & Gilbert (Pleuronectiformes: Paralichthyidae), caught in the Southern California Bight, U.S.A. These two species of Acanthochondria differ morphologically from their congeners by having a Type B-V antennule and elongate leg 2 rami (Type D), but can be distinguished from each other by differences in head shape, trunk shape, the relative size of the posterolateral processes of the trunk, the relative size of the abdominal somite, the insertion point of the caudal ramus, shape of the antennule tip, ornamentation of the antennal claw, ornamentation of the labrum, number of accessory teeth on the maxilliped claw, and ornamentation of legs 1 and 2 of the adult female. The taxonomic position of Acanthochondria zebriae Ho, Kim & Kumar, 2000 and A. bicornis Shiino, 1955 as well as the validity of the chondracanthid genus Pterochondria Ho, 1973 are also discussed.